The myth and reality of historic Nusantara Masjid architecture: Nusantara Islamic Architecture - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Denan, Zuraini; Abdul Majid, Noor Hanita; Abdullah, Fadzidah (2018)
As a masjid typology, historic Nusantara Masjid or vernacular masjid of South East Asia, its origin has been debated and basked in myth and mystery. The world history on Islamic architecture tapers at Mogul India  with Masjid architecture recognised by its typical form of Arab-Indian or Saracenic domes and arches  as well as built from masonry. It is only in passing does the historic vernacular masjid was addressed as particular identity of this region. The pyramidal timber Nusantara masjid form and architecture was presumed to be related to the Indianised world of pre-Islam and thus do not have its own form. Exploratory research through case studies was conducted on selected   available historic Nusantara masjid of  Malaysia and Indonesia. The purpose is to de-mystify its origin from the study of its stakeholders as well as from the masjid physical form through its tectonic, décor and composition. The findings, however, is regionally based. The masjid architecture of South East Asia  , although bear similarities with origin Rasulullah's SAW masjid in Madinah on its  plan shape and orientation, its formation, construct and detail, however, are very much intrinsic to who their stakeholders was, i.e.   the scholars, the nobilities or the royalties. Subject to how, when  and whom Islam was delivered and taught, as well as the architectural evolution through the layers of time especially under  colonisation, the Nusantara masjid , as a built form, remain a standalone typology of Islam in South East Asia. It, therefore, warrants a place in the world history of Islamic architecture as the sustainable regional architecture addressing not only the  intangible spiritual concerns of the Malay-Muslim community but also the regional culture, climate and economy in its physical manifestation true to its locality.